Unemployment, social factors and entrepreneurial skill acquisition among youths in Southwestern Nigeria - Iyanuoluwa, Adebo Adetumilara (2018)
There is mounting evidence that admits the biggest challenges many countries face are high unemployment rates and inadequate human capital investment. The young people are the most vulnerable to these endangerments. A young person is unemployed when he or she has not worked over a particular period but is willing to work and actively looking for work. The main purpose of the study is to address youth unemployment through social factors influencing entrepreneurial skills acquisition in Nigeria. Studies to date have contributed to literature on the factors influencing youth unemployment in Nigeria, However, it was observed that most of these studies are short of an in-depth understanding of the specific skills required during the entrepreneurial process in the Nigerian context; their studies also have methodological bias. To illuminate the skill acquisition concept and the processes involved in attaining mastery in a detailed context, this study intend to : 1) identify the attributes required for skill acquisition among youths in South-western Nigeria, 2) describe how much youths in South-western Nigeria have embraced skills acquisition, 3) determine the social factors influencing skill acquisition among youths in South-western Nigeria, and 4) determine the unique predictors (creativity, risk-taking propensity and entrepreneurial attitude) of entrepreneurial intention among youths in South-western Nigeria. This study employs a quantitative survey method supported by a qualitative interview, where the researcher combines elements of quantitative design with a semi structured interview in data collection process. A survey was conducted with 301 respondents based on sample size calculation. Four instruments were used as a basis of research instrument and these include 1) Entrepreneurship development designed by Pahurkar, Rajesh Narayanrao (2009), 2) The Entrepreneurship attitude orientation (EAO) scale by Robinson et al., (1991), 3) The risk propensity scale (RPS) by Lion & Meertens (2008) and 4) The creativity scale by Fields and Bischoff (2014). The data for the study was collected with the aid of a semi-structured interview schedule on various important themes; Such as (1) informants background, (2) Apprentices and requirements, (3) Skill level of artisan, (4) Skill level among ethnic group, (5) Access to financial Aid, (6) Entrepreneurial Attitude, and (7) Creativity. The result of the inteview schedule revealed that a readiness to entertain new ideas, patience and the ability to improvise are among the attributes required during the skill acquisition process. In contrast, occupational stereotypes, and an unwillingness to be subjected to the apprenticeship process were found to inhibit the youth’s acquisition of skills for production. Data collected using quantitative methods was analyzed using the Statistical Package for Social Sciences (SPSS) version 22. The result of the analysis revealed that the youth's level of education (p=0.001), Parents occupation (p=0.010) and respondents Occupation (0.031) were the major socioeconomic predictors of entrepreneurship skill acquisition among youths in the study. Likewise, a positive attitude towards entrepreneurship (p= 0.040) and creativity (p= 0.042) were the individual determinants positively related to entrepreneurial skill acquisition. In conclusion, the desire to obtain the financial rewards as well as an environment that is suitable for entrepreneurial activities were the major motivators of business venturing among Nigerian youths, but unwillingness to be subjected to the process of skill acquisition inhibit skill acquisition. Findings from the research contribute to the existing literature on skill acquisition and unemployment in Nigeria. This study also gives weight to the integrated behavioural model in singling out the importance of social and individual factors on the Intention to become entrepreneurs among young people. It also has implication for policymakers, education institutions, career counsellors and academicians at various levels, as it generates policy statements necessary for fashioning ways of reducing youth unemployment in Nigeria, boosting the attractiveness of entrepreneurship as a suitable option for job seekers and also the production of ‘Made in Nigeria’ goods.